FAKTOR-FAKTOR YANG MEMPENGARUHI CAPAIAN INDEK PENDIDIKAN DI KABUPATEN SAMBAS - B61112015, IWAN KUSNADI (Jurnal Ekonomi Daerah (JEDA), 2016)
This study aims to test and analyze the factors affecting educational attainment index, and a policy of what is being done to improve the educational attainment index in Sambas district. This study used a form of associative research with qualitative and quantitative approaches. The sources of data obtained from primary and secondary sources. Data analysis is done performed using non parametric statistical test Chi-Square with the help of statistical software SPSS 19.0 for Windows Version. From thisstudyconducted, the study showed that the factors of economic growth but not significant positive effect on educational attainment index in Sambas district. For factor income per capita is also positive but not significant effect on educational attainment index in Sambas district. Whereas for the education sector expenditure factor positive and significant impact on the outcomes of education index in Sambas district. Forwards, the shape of the policy pursued in the form of programs come on school, Bachelor Companion Program to Accelerate Improved Human Development Index (SP4-IPM), Proportional Distributions Teacher, Community Learning Center (PKBM), educationalsupport for poor families (junior high schoolÂ and senior high school), Regional School Operational Assistance (BOSDA), custom support for the poor, socialization/education on the importance of education, development of infrastructure and educational facilities, improving the quality of teachers, closer accessto higher education. Keywords : Economic Growth, Per Capita Income, Education Sector Spending, Education Index